2006
DOI: 10.3928/1081-597x-20060501-13
|View full text |Cite
|
Sign up to set email alerts
|

Late Traumatic Flap Dislocations After LASIK

Abstract: PURPOSE: To report the management and outcome of late onset traumatic dislocation of LASIK flaps. METHODS: This retrospective, interventional case series presents three patients with late onset LASIK flap dislocation following mechanical trauma 1 to 7 years postoperatively. RESULTS: In all cases, the flap was surgically repositioned. Epithelial ingrowth was removed and diffuse lamellar keratitis was treated with an intensive steroid regimen. All patients returned to their preoperative best … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 27 publications
0
32
0
1
Order By: Relevance
“…3,4 In the past 6 years, traumatic dislocation of LASIK flaps has been extensively reported, occurring perioperatively or even many years after the procedure. [5][6][7][8][9][10][11] However, traumatic loss of LASIK flaps has been reported rarely and generally occurs within the first 10 days following the procedure. 12,13 To our knowledge, this is the first report of traumatic loss of a LASIK flap occurring late postoperatively.…”
Section: J Cataract Refract Surg 2007; 33:1332-1335 Q 2007 Ascrs and mentioning
confidence: 99%
“…3,4 In the past 6 years, traumatic dislocation of LASIK flaps has been extensively reported, occurring perioperatively or even many years after the procedure. [5][6][7][8][9][10][11] However, traumatic loss of LASIK flaps has been reported rarely and generally occurs within the first 10 days following the procedure. 12,13 To our knowledge, this is the first report of traumatic loss of a LASIK flap occurring late postoperatively.…”
Section: J Cataract Refract Surg 2007; 33:1332-1335 Q 2007 Ascrs and mentioning
confidence: 99%
“…[5][6][7][8][9] A review of previous studies found only 1 case of a late traumatized LASIK flap involving half the total LASIK flap, which was dislocated and folded in half. 10 The patient presented to the clinic only 6 days after the trauma, with the dislocated LASIK flap doubled up and attached over the well-positioned original LASIK flap.…”
Section: Discussionmentioning
confidence: 99%
“…Further delay in treatment could have resulted in flap melting, increased scarring, and induction of irregular astigmatism. Flap macrostriae and epithelial ingrowth have been noted in several other cases of late flap dislocation (13 of 39 cases involved epithelial ingrowth, 7,10,11,14,15,18,20,24,26,27 and 19 cases reported flap striae 7,10-13,15-18,20,22,24,26,28,29,31 ); they tend to occur more frequently when there is a delay in presentation. When present, epithelial ingrowth and flap striae require special consideration during surgical repair.…”
Section: Days 27 )mentioning
confidence: 91%
“…15 Several authors report the use of BSS to irrigate and refloat the flap. 7,9,16,23,24,28 After manipulation and repositioning, some cases report the use of glue 12 or nylon sutures 8,9,11,13,14 to secure the flap in place. Application of a bandage contact lens was commonly reported.…”
Section: Days 27 )mentioning
confidence: 98%